Tháng Tư 19, 2024

Tính giá trị của các biểu thức \(M = \sqrt {36} + \sqrt {25} \) \(N = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} – \sqrt 5 \) A \(M = 1\,\,\,\,;\,\,\,\,N = 2\sqrt 5 \) B \(M = 11\,\,\,\,;\,\,\,\,N = – 1\) C \(M = – 11\,\,\,\,;\,\,\,\,N = 1\) D \(M = – 1\,\,\,\,;\,\,\,\,N = – 2\sqrt 5 \)

Tính giá trị của các biểu thức

\(M = \sqrt {36} + \sqrt {25} \) \(N = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} – \sqrt 5 \)

A \(M = 1\,\,\,\,;\,\,\,\,N = 2\sqrt 5 \)

B \(M = 11\,\,\,\,;\,\,\,\,N = – 1\)

C \(M = – 11\,\,\,\,;\,\,\,\,N = 1\)

D \(M = – 1\,\,\,\,;\,\,\,\,N = – 2\sqrt 5 \)

Hướng dẫn Chọn đáp án là: B

Phương pháp giải:

Sử dụng công thức: \(\sqrt {{A^2}B} = \left| A \right|B = \left\{ \begin{array}{l}AB,\,\,A \ge 0\\ – AB,\,\,A < 0\end{array} \right.\)

Lời giải chi tiết:

\(M = \sqrt {36} + \sqrt {25} \) \(N = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} – \sqrt 5 \)

Ta có: \(M = \sqrt {36} + \sqrt {25} = \sqrt {{6^2}} + \sqrt {{5^2}} = 6 + 5 = 11\)

\(N = \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} – \sqrt 5 = \left| {\sqrt 5 – 1} \right| – \sqrt 5 = \sqrt 5 – 1 – \sqrt 5 = – 1\,\,\left( {Do\,\sqrt 5 – 1 > 0\,\,} \right)\)

Chọn B.